Health aspects of plumbing. (World Health Organization ; World Plumbing Council, 2006)
This publication describes the processes involved in the design, installation and maintenance of modern plumbing systems. It recommends a number of plumbing system design and installation specifications that have demonstrated their validity from years of experience. It also examines the microbiological, chemical, physical and financial risks associated with plumbing, and outlines the major risk management strategies that are used in the plumbing industry and emphasizes the importance of measures to conserve supplies of clean water. This work is dedicated to assisting developing countries in ac.